Effect of management practices on mycorrhizal infection, growth and dry matter partitioning in field-grown bean - Oliveira, Antonio Alberto Rocha; Sanders, Francis Edward (Pesquisa Agropecuaria Brasileira, 1999)
The experiment was carried out on unsterilized field soil with low phosphorus availability with the objective of examining the effect of cultural practices on mycorrhizal colonization and growth of common bean. The treatments were: three pre-crops (maize, wheat and fallow) followed by three soil management practices ("ploughing", mulching and bare fallow without "ploughing" during the winter months). After the cultural practices, Phaseolus vulgaris cv. Canadian Wonder was grown in this soil. Fallowing and soil disturbance reduced natural soil infectivity. Mycorrhizal infection of the bean roots occurred more rapidly in the recently cropped soil than in the fallow soil. Prior cropping with a strongly mycorrhizal plant (maize) increased infectivity even further.